Integrasi Nilai Filsafat Pendidikan Islam dalam Kurikulum Merdeka: Analisis Konseptual terhadap Pendekatan Deep Learning - Yulinda; Sufarhan; Ruslan; Muslimin; Irfan; Nurfaigah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study examines the integration and implementation of the values of Islamic educational philosophy in the learning process. The objectives of this study are: (1) to explain the concept of integrating the values of Islamic educational philosophy into the Merdeka Curriculum, (2) to analyze the role of the Deep Learning approach in its application, and (3) to identify effective strategies for internalizing the values of Islamic educational philosophy in learning. The method used is a literature review by analyzing various scientific sources related to Islamic educational philosophy and learning. The research findings indicate that the integration of Islamic educational philosophy values can be achieved by linking curriculum content to moral and spiritual values. This can be implemented in the classroom through class discussions, experiential learning activities that draw on local and Indonesian cultures, and teachers setting a good example in their daily lives within the school environment. This approach helps students understand and apply Islamic values in their lives and supports the development of knowledge, positive attitudes, and social and spiritual responsibility. In conclusion, these findings affirm that integration that is purposeful and supported by a Deep Learning approach can create meaningful learning and contribute to the holistic character development of students.